Leveraging Blockchain technology to accelerate financial and nonfinancial inclusion and empowerment in developing countries - Gohar, Ali (Vojnotehnički glasnik / Military Technical Courier, 2024)
Introduction/purpose: Blockchain is a technology that first came into existence to optimize the cryptocurrency area by forming a decentralized network for online transactions and managing investors’ data. With the advent of technology, new ideas have started taking shape in experts’ minds regarding the potential of this technology if it were to be used in areas other than just cryptocurrency – mainly Bitcoin. Some of its potential features include security, distributed data, maintaining data integrity, anonymity, and the lack of need for third-party involvement. This research has analyzed the use of Blockchain technology in Pakistan, including its awareness amongst technical experts and the public. The focus areas are using Blockchain technology in hospitals as well as for voting, political documents, financial ledgers, and contracts. The research aimed to investigate which field is most appropriate to use Blockchain technology according to the general public belief. Methods: A detailed survey has been carried out collecting answers from the public, and gathering expert opinions on the topic. The TOPSIS approach was then applied to determine which fields are the most favored. Results: The results favored the use of Blockchain technology in the areas of political documentation. Based on the conducted study, there are recommendations and important insights provided from experts to facilitate the improvement of the system in Pakistan. Conclusion: In conclusion, this study sets out to understand public and expert perspectives on using Blockchain technology in other sectors of the country. As a result of this research work, it is concluded that government/political documentation presents an exciting market for implementing this technology.